A decision support system for quality control - Aktan, Fikret Ümit. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
The important role df Quality Control in the economic growth of Turkey has become a well-known fact, especially in the last few years when Turkey has increased her efforts for expanding the exports. However, Quality Control is not understood and utilized effectively as a management tool in most of the Turkish industrial companies. There exists a large gap between the practical applications and the theoretical developments in statistical quality control techniques, due to a lack of understanding of QC by managers. In this study, Decision Support Systems (DSS) are proposed as a tool that would be helpful in filling this gap, by leading the managers towards the use of scientific management approach in making decisions related to quality improvement. Quality Control activities are conducted through various decisions ranging from short-term to long-term taken at different levels of management. In this study, only one of these decisions is taken into consideration and it is aimed to give support to one of the basic activities of QC, namely the feedback mechanism between production and management. Thus, a decision support system is designed to aid the management in fighting with the chronic quality problems, in away to provide a set of capabilities expected· from a DSS, in general. This decision support system which will be called QCDSS, is an in teractive computer-based system which helps the decision-maker in the identification of vital chronic quality problems, and in the evaluation of possible precautions that can be taken to give remedy. QCDSS combines flexible, ad hoc data analysis capabilities with some models. This integration is achieved through a user-friendly dialog component. The problem identification phase of the decision is supported by a systematic Pareto analysis model which will be called "Failure Analysis Module" while a Monte-Carlo simulation model embedded in the "Revision of the Inspection Plan Module" is utilized to support the alternative evaluation phase. QCDSS is developed for a light bulb manufacturing company where production is continuous and controls are by attributes.
Keywords: Quality control.; Decision making.